MiR‐210 Links Hypoxia With Cell Proliferation Regulation in Human Laryngocarcinoma Cancer. Issue 6 (10th April 2015) - Zuo, Jianhong; Wen, Meiling; Lei, Mingsheng; Peng, Xiang; Yang, Xuefeng; Liu, Zhigang
ABSTRACT: The microRNA hsa‐miR‐210 (miR‐210) is associated with hypoxia; however its function has not fully identified. In the present study, we aim to detect its role concerning proliferation in Laryngocarcinoma. We found that miR‐210 was highly expressed in hypoxia, which inhibited proliferation by inducing cell cycle arrest in G1/G0 as well as apoptosis. We further identified that miR‐210 targeted fibroblast growth factor receptor‐like 1 (FGFRL1). Down regulation of FGFRL1 decreased cell proliferation by promoting proportion of cells in G1/G0 phase and decreasing in S and G2/M phases. Moreover, overexpression of FGFRL1 effectively released the miR‐210‐induced suppression of SCC10A cell proliferation. Expression of miR‐210 repressed tumor xenograft growth in vivo as well. Together, our findings reveal a new mechanism of adaptation to hypoxia that miR‐210 inhibits the proliferation via inducing cell cycle arrest and apoptosis by the targeting of FGFRL1. J. Cell. Biochem. 116: 1039–1049, 2015. © 2015 Wiley Periodicals, Inc.